Deciphering the role of Wnt/β-catenin and miR-214 in knee osteoarthritis: molecular and clinical insights - Waad A. Samman; Esraa M. Mosalam; Esraa M. Mosalam; Dalia S. Saif; Mahmoud S. Abdallah; Mahmoud S. Abdallah; Abdel-Aziz A. Zidan; Amany Said Sallam; Shimaa Abdelsattar; Fatma Omar Khalil; Amany E. Elashkar; Somia Mokabel Mohamed; et al. (Frontiers in Pharmacology)
IntroductionUnderstanding the molecular mechanism underlying the pathogenesis of knee osteoarthritis (KOA) may be beneficial in fetching new therapeutics. Our study aims to investigate the implication of Wnt/ β-catenin pathway in development of KOA by detection of the downstream target genes and their crosstalk with miR-214 in patients with KOA and to correlate that with the clinical findings.MethodsSixty participants were involved in the study. The levels of miR-214, β-catenin, Wnt4, matrix metalloproteinase 3 (MMP3), Bax, caspase 3, and phosphorylated glycogen synthase kinase-3 beta (pGSK3β) were determined. All participants were assessed clinically and radiologically regarding knee joint pain, stiffness, range of motion, and knee medial cartilage thickness. Besides, a correlation between Western Ontario and McMaster Universities (WOMAC) score, clinical, and radiological data, and the measured parameters was conducted.Results and discussionPatients with KOA showed downregulated miR-214 with upregulated β-catenin, Wnt4, MMP3, Bax, caspase 3, and pGSK3β compared to healthy individuals. Statistically significant positive correlation between WOMAC score, knee joint pain regarding Visual Analogue Scale (VAS) with β-catenin, pGSK3β, Wnt4, MMP3, Bax, and caspase 3, and significant negative relationship between them and knee joint medial cartilage thickness; while there was a statistically significant negative correlation between WOMAC, and clinical findings of osteoarthritis and miR-214 and significant positive relationship between it and knee joint medial cartilage thickness. This study provides valuable insights into involvement of the Wnt/β-catenin and miR-214 in KOA pathogenesis. By targeting these molecular components, future therapeutics may modulate their activity and mitigate chondrocyte apoptosis and matrix degradation, potentially halting KOA progression.